2014
DOI: 10.1038/modpathol.2014.54
|View full text |Cite
|
Sign up to set email alerts
|

Re-evaluating the role of sentinel lymph node biopsy in microinvasive breast carcinoma

Abstract: The role of sentinel lymph node biopsy in microinvasive breast carcinoma is unclear. We examined the incidence of lymph node metastasis in patients with microinvasive carcinoma who underwent surgery at our institution. Retrospective review of our pathology database was performed (1994-2012). Of 7000 patients surgically treated for invasive breast carcinoma, 99 (1%) were classified as microinvasive carcinoma. Axillary staging was performed in 81 patients (64, sentinel lymph node biopsy; 17, axillary lymph node … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 46 publications
4
16
0
Order By: Relevance
“…The findings of this study indicate that SLNB may not be useful in microinvasive DCIS owing to the low risk of lymph node metastasis and good prognosis. The good prognosis may be explained by the theory that the major rate of positivity could correspond to an iatrogenic transit of tumour/epithelial cells to lymph nodes, without the significance of real metastasis. Level 1 evidence shows that, in patients with SLN‐positive breast cancer, axillary dissection may be avoided when there is a low axillary metastatic burden (Z0011) and in patients undergoing BCS with radiotherapy; this also supports the conclusion that SLNB in microinvasive DCIS may not be useful.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings of this study indicate that SLNB may not be useful in microinvasive DCIS owing to the low risk of lymph node metastasis and good prognosis. The good prognosis may be explained by the theory that the major rate of positivity could correspond to an iatrogenic transit of tumour/epithelial cells to lymph nodes, without the significance of real metastasis. Level 1 evidence shows that, in patients with SLN‐positive breast cancer, axillary dissection may be avoided when there is a low axillary metastatic burden (Z0011) and in patients undergoing BCS with radiotherapy; this also supports the conclusion that SLNB in microinvasive DCIS may not be useful.…”
Section: Discussionmentioning
confidence: 99%
“…If staging the axilla in DCIS is accepted globally in the above conditions, what remains controversial is the real value of staging the axilla with SLNB in microinvasive DCIS, as reviewed in Table . The incidence of axillary metastasis in sentinel nodes varies in studies from approximately 2 to 20 per cent.…”
Section: Introductionmentioning
confidence: 99%
“…The rate of axillary lymph node metastasis is approximately 0% to 20% in DCIS-MI. [29][30][31][32][33][34][35][36] It is crucial to distinguish between clinical node positivity and node negativity with positive sentinel lymph node biopsy (SLNB). SLNB is a standard examination for patients with breast cancer and clinically negative lymph nodes.…”
Section: Management Of Axillary Lymph Nodes Dcis-mimentioning
confidence: 99%
“…However, in a recent study investigating the role of SLNB in DCIS-MI, Magnoni and colleagues 33 found that SLNB was not a good predictor of the need for ALND. Among 257 women with microinvasive breast cancer, 87.9% (266) had negative SLNB, and 12.1% (31) had positive SLNB. Among the 31 patients with positive SLNB, 5, 14, and 12 patients had macrometastases, micrometastases, and isolated tumor cells in sentinel nodes, respectively.…”
Section: Management Of Axillary Lymph Nodes Dcis-mimentioning
confidence: 99%
“…The clinical and prognostic significance of a minimal tumor burden in the axilla of breast cancer patients is unclear (6). ITCs are defined as small clusters of tumor cells not greater than 0,2 mm or clusters of cells not exceeding 200 cells in a single lymph node cross section.…”
mentioning
confidence: 99%